Functional MRI Investigation of Ultrasound Stimulation at ST 36. (22nd February 2020) - Wei, Yarui; Mei, Ling; Long, Xiaojing; Wang, Xiaoxiao; Diao, Yanjun; Nguchu, Benedictor A.; Hu, Sheng; Wang, Yanming; Yu, Haibo; Qiu, Bensheng
Abstract : Background . Clinical and experimental data suggest that ultrasound stimulation (US) at acupoints can produce similar effective treatment compared to manual acupuncture (MA). Although the brain activation to MA at acupoints is investigated by numerous studies, the brain activation to US at acupoints remains unclear. Methods . In the present work, we employed task state functional magnetic resonance imaging (fMRI) to explore the human brain's activation to US and MA at ST 36 ( Zusanli ) which is one of the most commonly used acupoints in acupuncture-related studies. 16 healthy subjects underwent US and MA procedures in an interval of more than one week. On-off block design stimulation was used for the recording of fMRI-related brain patterns. Results . Both US and MA at ST 36 produced activations in somatosensory and limbic/paralimbic regions (postcentral gyrus, insula, middle prefrontal cortex, and anterior cingulate cortex). Only US at ST 36 produced a significant signal increase in the inferior parietal lobule and decrease in the posterior cingulate cortex, whereas MA at ST 36 produced a significant signal increase in the lentiform nucleus and cerebellum. Conclusions . Our results indicate that US may be a possible noninvasive alternative method to MA due to its similar activation patterns.